2010
DOI: 10.1088/0957-4484/21/42/425301
|View full text |Cite
|
Sign up to set email alerts
|

Tailored antireflective biomimetic nanostructures for UV applications

Abstract: Antireflective surfaces composed of biomimetic sub-wavelength structures that employ the 'moth eye principle' for reflectance reduction are highly desirable in many optical applications such as solar cells, photodetectors and laser optics. We report an efficient approach for the fabrication of antireflective surfaces based on a two-step process consisting of gold nanoparticle mask generation by micellar block copolymer nanolithography and a multi-step reactive ion etching process. Depending on the RIE process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Bernhard observed that the outer surface of corneal lenses of moths is covered with an ordered array of conical protuberances, typically of about 200 nm height and spacing [79,80]. Such a bioinspired structure was then realized by Clapham and Hutley [80] (followed by many other researchers in different forms [81,82]) on glass (although it can be realized on any reflective surface) where the coating reduced the reflection of the glass from 5.5% to 0.2%. Although the results were impressive, the developed coating was very delicate and not very applicable [80].…”
Section: Conventional Antireflective Coatings (Arcs)mentioning
confidence: 99%
“…Bernhard observed that the outer surface of corneal lenses of moths is covered with an ordered array of conical protuberances, typically of about 200 nm height and spacing [79,80]. Such a bioinspired structure was then realized by Clapham and Hutley [80] (followed by many other researchers in different forms [81,82]) on glass (although it can be realized on any reflective surface) where the coating reduced the reflection of the glass from 5.5% to 0.2%. Although the results were impressive, the developed coating was very delicate and not very applicable [80].…”
Section: Conventional Antireflective Coatings (Arcs)mentioning
confidence: 99%
“…Nowadays, different technologies are used for the commercial production of these subwavelength structures. Either stochastic surface structures are fabricated by maskless plasma etching or more or less periodic structures can be written with IFL or e-beam lithography, or self-organized surface layers are used as a mask for structuring (e.g., Morhard et al [18]) (see Figure 7). …”
Section: Grating Types According To Applicationmentioning
confidence: 99%
“…Outside nature-inspired applications, textured surfaces show promising optical properties, both as transmissive and reflective diffraction gratings [4,5]. Designing topographies on a surface can lead to applications in photonics (such as nanostructured polarizers and/or wave plates [6,7] and antireflection coatings [8][9][10][11]), friction control (including robotic fingerprints [12,13]), (de)wetting of surfaces and even control over cellular adhesion and mobility [14].…”
Section: Introductionmentioning
confidence: 99%